The BETWEEN TRADITIONAL AND IMPROVISATION: FOOD AS A SYMBOL IN DIANA ABU-JABER’S MEMOIRS - Salsabila Ramadhania (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This paper examines how Diana Abu-Jaber's works, The Language of Baklava (2005) and Life Without a Recipe (2016), describe how Muslim women negotiate identity and freedom amid the pressures of tradition (culture) and diaspora. Both works show a shift in the meaning of women's identity from obedience to cultural and family values towards the search for autonomy and self-identity. Previous studies have focused more Abu-Jaber's work from the perspective of nostalgia and hybridity, but often ignore the transformative role of food as a feminist language for self-expression. Therefore, using food studies theory from Anny Gaul (2024), feminist theory from Amir Aziz (2025), the concept of bildungsroman from Franco Moretti (2000), and the theory of hybridity and third space from Homi Bhabha (1994), this study aims to explore how food functions as a symbol of both cultural preservation and personal freedom for Muslim women in Abu Jaber's memoirs. This study interprets the process of women's transformation from cultural preservation to active subjects who reconstruct the meaning of freedom through daily activities. The results of the study show that Abu Jaber not only writes about food, but also uses experiences related to food as a metaphor for the journey of Muslim women in the diaspora. Thus, this study confirms the effort to negotiate a space of autonomy between culture, religion, and modernity. Keywords: This paper examines how Diana Abu-Jaber's works, The Language of Baklava (2005) and Life Without a Recipe (2016), describe how Muslim women negotiate identity and freedom amid the pressures of tradition (culture) and diaspora. Both works show a shift in the meaning of women's identity from obedience to cultural and family values towards the search for autonomy and self-identity. Previous studies have focused more Abu-Jaber's work from the perspective of nostalgia and hybridity, but often ignore the transformative role of food as a feminist language for self-expression. Therefore, using food studies theory from Anny Gaul (2024), feminist theory from Amir Aziz (2025), the concept of bildungsroman from Franco Moretti (2000), and the theory of hybridity and third space from Homi Bhabha (1994), this study aims to explore how food functions as a symbol of both cultural preservation and personal freedom for Muslim women in Abu Jaber's memoirs. This study interprets the process of women's transformation from cultural preservation to active subjects who reconstruct the meaning of freedom through daily activities. The results of the study show that Abu Jaber not only writes about food, but also uses experiences related to food as a metaphor for the journey of Muslim women in the diaspora. Thus, this study confirms the effort to negotiate a space of autonomy between culture, religion, and modernity.